Connectivity of Actors and Diffusion of Ideas in HR Systems Configuration Process in Multinational Subsidiaries in Indonesia - Rupidara, Neil Semuel (Universitas Prasetiya Mulya, 2018)
Human Resource (HR) literature tends to overlook the process of HR systems configuration. Researching the process, this article particularly examines the phenomenon of connectivity and the diffusion of ideas among HR actors and other actors outside companies. Three case studies of multinational subsidiaries in Indonesia were conducted. Data were collected through interviews, observations, and corporate documents and were analyzed using a modified-grounded approach. The findings show similarities among elements of HR systems across the cases, showing connectivity of ideas and actors in the configuration process. The ideas constituting the HR systems within each company were adopted through a variety of channels of diffusion. This article proposes a typology of connectivity of actors that enables the diffusion and adoption of ideas across companies.